Different methods of grafting and activity of antioxidant enzymes in tomato - De Sousa Da Silva, Edvar (2016)
Mechanical injuries caused during grafting can induce oxidative stress, causing deleterious effects on the cells. This study aimed to evaluate the damage caused by grafting methods in tomato plants by assessing the enzymatic activity of superoxide dismutase, catalase, peroxidase and polyphenoloxidase and assessing phenol content. Three grafting methods were applied to the 'Guardião'® rootstock (bevel contact, cleft and approach grafting), as well as the 'Pizzadoro'® tomato free-standing plant and five sampling periods (0, 3, 6, 9 and 12 days after grafting). The grafting methods employed did not induce changes in catalase activities. There was alteration in peroxidase activity in response to bevel contact and cleft grafting. Plants showed higher polyphenol oxidase activity after 12 days of grafting in all grafting methods. Total content of phenols in grafted plants did not differ from the free-standing. The results suggest compatibility between rootstock and graft. The survival rate indicates that the methods employed were appropriate. The most recommended grafting methods for tomato are bevel contact and cleft grafting, depending on the survival rate.